D01 The influence of menstrual cycle phase on isokinetic strength of the knee flexors and extensors - Quigley, Taweoo; Greig, Matt (Graduate Journal of Sports Science, Coaching, Management, & Rehabilitation, 2024)
The increased incidence of anterior cruciate ligament (ACL) injury in female football players has been associated with hormonal variations during the menstrual cycle (MC). The MC has potential to compromise the functional characteristics of thigh muscle with implications for strength, knee joint stability and ACL injury risk. The isokinetic dynamometer is the gold standard for assessing strength, but previous studies have considered only concentric knee flexor and extensor strength. This lacks functional relevance to the mechanism of ACL injury and negates the role of eccentric hamstring strength. Furthermore, isokinetic studies typically report peak torque as the objective measure of strength which limits analysis of the strength curve to a single, maxima. The aim of the current study was to evaluate the influence of MC phase on the strength profile of female football players, utilising a range of speeds to reflect the varying demands of football and adopting more contemporary metrics to quantify the strength curve. Eight, eumenorrheic, recreational football players completed eccentric knee flexor and concentric knee extensor trials at 60 and 240°·s−1 during the follicular (Day 2), ovulation (Day 14) and luteal (Day 21) phases of their MC. In a pre-experimental test, MC tracking app via mobile phone and ovulation strips were used to identify the phases of the MC. The experimental protocol has been previously approved by Edge Hill university ethics committee. Peak torque and corresponding angle of peak torque were maintained across all phases of the MC, irrespective of testing modality and speed. Strength ratios defined using peak torque were also not sensitive to MC phase. However, Functional Range in eccentric knee flexion was significantly lower during the follicular phase (16.36 ± 5.15°), compared to ovulation phase (21.15 ± 5.02°; P = 0.009) and luteal phase (20.69 ± 4.62°; P = 0.018), which were themselves not different (P = 0.797) at both testing speeds. This supports epidemiological observations but highlights the importance of analysing isokinetic data beyond the peak of the strength curve. The reduced Functional Range reflects a reduction in eccentric hamstring strength towards knee extension, where the ACL injurious mechanism is likely to occur. Interpretation of isokinetic data should therefore focus on points of ‘weakness’ as opposed to maximum strength, whilst (p)rehabilitative strategies should consider strength through range of motion, and at different speeds. Eccentric hamstring strength was observed to decrease significantly at the higher speed, contrary to observations in elite male players, and potentially reflecting a differential training adaptation.